ANALISIS KEKUATAN LENTUR DAN DAKTILITAS PADA PENAMPANG KOLOM BETON BERTULANG, KOLOM BAJA DAN KOLOM COMPOSITE DENGAN SOFTWARE ‘XTRACT’ - Rudy Tiara (Jurnal Teknik Sipil USU, 2014)
Abstract Ductility and flexural strength are two important parameters in designing columns. Moment-curvature curve can be used to determine the ductility of columns. In this paper, moment-curvature analysis is conducted to investigate the effect of some parameters on flexural strength and ductility of reinforced concrete columns, steel reinforced concrete columns and steel columns. The parameters are longitudinal bar area, transverse reinforcement spacing, steel section area and its shape, concrete strength, longitudinal and transverse rebar yield strength. The analysis is conducted by using ‘XTRACT’. Analysis results show that closer transverse spacing, lower concrete strength and lower longitudinal bar yield strength increase the ductility of RC columns. However, bigger longitudinal bar area and lower transverse rebar yield strength decrease the ductility. In addition, the configuration of longitudinal bars may influence the ductility of columns. SRC column with H-shaped steel has a higher ductility than that with I-shaped steel since H-shaped steel provides higher confinement effect than I-shaped steel. Keywords : Ductility and Flexural Strength, Moment-Curvature Analysis, Confinement Effect.